ANALISIS FAKTOR - FAKTOR YANG DAPAT MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT PONTIANAK KOTA - B31106011, Wilia Kartisari (Jurnal Manajemen Update, 2013)
This study analyzes the relationship called motivation with employee performance PT. Matahari Departement Store Tbk Cabang Pontianak. Problem in this study is how the relationship motivation relationship with work performance at PT. Matahari Departement Store Tbk Cabang Pontianak. Purpose of this study way to determine the relationship of motivation to employee performance PT. Matahari Departement Store Cabang Pontianak. The research method used is descriptive method using a questionnaire interview and observation as data collection techniques. The population in this study all employee at PT. Matahari Departement Store Tbk Cabang Pontianak. Data were analyzed qualitatively on the answers of the respondents were processed using Microsoft Excel 2007 and the application program SPSS version 19.0 statistical. These result it can be concluded that the motivations apparently significantly related to job performance of employees who will then support the implementation of the tasks and function of each in the improvement and development of the company PT. Matahari Departement Store Cabang Pontianak. Key words : motivation, job performance